ELEMENTARY SIMPLE SENTENCES WITH A NOMINAL PREDICATE I N TURKIC LANGUAGES: TWO-ACTANT MODELS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The paper discusses the grammatical nature of two-actant elementary simple sentences with a nominal predicate. Nominal predicates in the syntaxemes determine the presence of two actants. Models represent the unity of a structural scheme and a proposition. The proposition is addressed to objective reality and to language.
Keywords: elementary simple sentence, model, structural scheme, proposition, variant